Competitive strategy for Luxury hotel resorts in Phuket : gaining competitive advantage through environmentally friendly development - Arnfinn Oines (Prince of Songkla University, 2006)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2006